Efektivitas Dakwah dan Kolaborasi Pemerintah dalam Menanggulangi Pernikahan Dini di Provinsi Jawa Tengah - Yuliana, Efa; Salsabila, Putrinala; Fadhilah, Evana Winny; Setiyadana, Dewi Rahmawati; Khasanah, Nala Fauziah; Septiana, Nicean; Rofiq, Nur (Maddah: Journal of Advanced Da'wah Management Research, 2024)
Child marriage in Central Java remains a serious issue with significant impacts on health, education, and community welfare. According to data from the Semarang Religious Court in 2020, there was a substantial increase of 45% in requests for marriage dispensations. Child marriage not only increases health risks for mothers and children but also leads to school dropout, economic hardship, and the perpetuation of poverty cycles. This study aims to analyze the effectiveness of da'wah (Islamic outreach) in raising public awareness about the dangers of child marriage and the collaborative role of da'wah and the government in addressing this phenomenon. The research method employed a literature review, gathering, analyzing, and synthesizing information from journal articles, books, research reports, and other reliable sources. The findings indicate that da'wah plays a strategic role in educating the public through continuous delivery of moral, religious, and social messages. Collaboration between da'wah and the government creates an effective synergy in transforming social norms, strengthening regulations, and increasing awareness of the importance of education and the negative impacts of child marriage. Therefore, a holistic approach involving both elements can serve as a sustainable solution to address child marriage in Central Java.